PARENTING PREPARATION EDUCATION IMPROVES SELF EFFICACY IN PREGNANT WOMEN - Nuria Dianita Murwika; Machria Rachman; Fransisca Retno Asih (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: In Indonesia, 42.3% of pregnant women have low self-efficacy and 68.7% women are not physically and knowledge-wise ready to become mothers. Willingness to become parents is very important to create a better future generation. Education with audio-visual media is preferred and easy to understand. This study aims to determine the effect of education on preparation for becoming parents on the self-efficacy of pregnant women. Method: The design of this study was a quasi-experimental design with a pre-test post-test non-equivalent with control group design approach, which was conducted at the Songgon Health Center Banyuwangi, Indonesia in June 2024. The sample size consisted of 36 people selected through purposive sampling. The subjects of this study, pregnant women who met the inclusion and exclusion criteria, were divided into two groups: the intervention group (18 respondents), which received educational animated videos on parenthood preparation, and the control group (18 respondents), which received standard ANC interventions. Self-efficacy was measured using the Maternal Self-Efficacy in Parenting Preparation questionnaire.  The statistical analysis was conducted using the Mann-Whitney and Wilcoxon tests. Result: The average increase in self-efficacy in the intervention group was greater than in the control group (10.72> 5.50). The results of the statistical test showed a p-value of 0.019 (p <0.05), namely there was an effect of education on preparation for becoming parents on the self-efficacy of pregnant women. Conclusion: Education about preparing to become parents using animated videos can be applied during pregnancy classes or during antenatal care.